PKM Peningkatan Daya Saing UMKM Melalui Inovasi Desain Dan Kemasan Produk Makanan - Denni Pratama; Arif Rinaldi Dikananda; Ahmad Faqih; Cistia Ningrum; Lukman Dwi Kusuma (AMMA : Jurnal Pengabdian Masyarakat, 2024)
MSMEs in the food sector play a crucial role in Indonesia's economy. However, the competitiveness of MSME products remains low due to a lack of innovation in product design and packaging. This issue hinders broader market penetration and reduces consumer interest. This program aims to enhance the competitiveness of MSME products through innovative and functional design and packaging. The methods employed include design training and workshops, as well as mentoring in implementing new packaging. The expected outcome is an improvement in the quality of product design and packaging, which can attract more consumers and boost sales. Consequently, MSMEs can compete more effectively in both local and international markets.